Impact of COVID-19 and lockdown on mental health of children and adolescents: A narrative review with recommendations (2020)
Background: COVID-19 pandemic and lockdown has brought about a sense of fear and anxiety around the globe. This phenomenon has led to short term as well as long term psychosocial and mental health implications for children and adolescents. The quality and magnitude of impact on minors is determined by many vulnerability factors like developmental age, educational status, pre-existing mental health condition, being economically underprivileged or being quarantined due to infection or fear of infection. Aims: This paper is aimed at narratively reviewing various articles related to mental-health aspects of children and adolescents impacted by COVID-19 pandemic and enforcement of nationwide or regional lockdowns to prevent further spread of infection. Methodology: We conducted a review and collected articles and advisories on mental health aspects of children and adolescents during the COVID-19 pandemic. We selected articles and thematically organized them. We put up their major findings under the thematic areas of impact on young children, school and college going students, children and adolescents with mental health challenges, economically underprivileged children, impact due to quarantine and separation from parents and the advisories of international organizations. We have also provided recommendations to the above. Conclusion: There is a pressing need for planning longitudinal and developmental studies, and implementing evidence based elaborative plan of action to cater to the psycho social and mental health needs of the vulnerable children and adolescents during pandemic as well as post pandemic. There is a need to ameliorate children and adolescents’ access to mental health support services geared towards providing measures for developing healthy coping mechanisms during the current crisis. For this innovative child and adolescent mental health policies policies with direct and digital collaborative networks of psychiatrists, psychologists, paediatricians, and community volunteers are deemed necessary.